Analisis Fraud Hexagon dalam Kasus Korupsi di PT Pertamina Patra Niaga - Fitriani, Qonita; Sugiarti, Erika; Fadhilah, Husni; Munyani Putri, Fiqi; Novaria Misidawati, Dwi (Yayasan Cendekia Gagayunan Indonesia, 2025)
This research is motivated by the rampant corruption cases in the State-Owned Enterprises (BUMN) environment, especially at PT Pertamina Patra Niaga. The main objective of this research is to identify and analyze the factors that cause corruption using the Fraud Hexagon analysis framework. The research method used is a descriptive qualitative approach, with data collection techniques through literature studies from various scientific literature, journals, mass media coverage, and relevant official documents. The results showed that corrupt practices at PT Pertamina Patra Niaga were influenced by six main elements in the Fraud Hexagon model, namely pressure, opportunity, rationalization, capability, arrogance, and collusion. Pressure comes from the lifestyle and job demands of the perpetrator; opportunities arise due to a weak supervisory system and imperfections in the procurement process; rationalization occurs through moral justification for acts of corruption. The capability of perpetrators who occupy strategic positions allows collusion with internal and external parties, which is exacerbated by arrogance. These six elements are interrelated and form a systemic pattern that supports corruption. This research confirms the importance of strengthening the internal control system, instilling an integrity-based organizational culture, and implementing a transparent and reliable reporting system to prevent corrupt practices within SOEs.